Criminal Legal Protection for Bona Fide Third Parties Over Assets in Corruption and Money Laundering Cases - Arief Patramijaya (Faculty of Law, Sriwijaya University, Indonesia, 2024)
Criminal law in Indonesia has yet to guarantee justice and human rights of bona fide (good faith) third parties in protecting their confiscated assets in corruption and money laundering cases. Criminal procedural law is inadequate in providing assessments for bona fide third parties. Therefore, Economics and Anthropology are needed in the investigation stage up to the evidentiary stage during trials. In this research, the main problems are formulated as follows: (1) what is the concept, definition, and scope of the assets of third parties in good faith in the laws and regulations in Indonesia? (2) how is the application of legal provisions regarding the protection of third parties with good intentions in corruption and money laundering? (3) what is the ideal role of the Public Prosecutor and Judge in protecting the property of a third party with good intentions in the criminal justice system? Normative law research conducted in this article showed that (1) the concept and understanding of bona fide third parties in civil law can be adopted in criminal law; (2) the application of legal protection to bona fide third parties over their assets in corruption and money laundering cases still depends on the moral goodness of law enforcement officials; and (3) investigators, prosecutors, and judges play an important role in protecting the human rights of bona fide third parties in corruption and money laundering cases.